Mesoporous Vanadium Nitride Synthesized by Chemical Routes - Pragnya P. Mishra; J. Theerthagiri; Rabi N. Panda (Adsorption Science & Technology)
Nanocrystalline vanadium nitride (VN) materials are synthesized by two different routes, namely, the urea route and the ammonia route, using various V 2 O 5 precursors obtained by citric acid–based sol–gel method. The VN nanomaterials obtained are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and BET method. The XRD patterns show the presence of pure cubic phase with line broadening. The lattice parameters were found to be 4.1266 and 4.1136 Å for the urea route and 4.1125 and 4.1120 Å for the ammonia route using V 2 O 5 precursors heat treated at 350 and 550 °C, respectively. The estimated crystallite sizes are found to be 9 and 7 nm for the urea route and 22 and 28 nm for the ammonia route using V 2 O 5 precursors synthesized at 350 and 550 °C, respectively. The SEM images show the presence of agglomerates having particle dimensions of 115 and (300 × 15) nm for the urea route and 111 and 68 nm for the ammonia route using V 2 O 5 precursors heat treated at 350 and 550 °C, respectively. The maximum BET surface area of 57 m 2 /g was obtained for VN sample synthesized by the urea route using V 2 O 5 precursors synthesized at 350 °C. The isotherms show typical Type IV with H2 hysteresis, which is characteristic of the mesoporous particles. The production of high-surface-area nitride materials has been correlated to synthetic procedure, precursor used and formation of mesopores in the material.